HUBUNGAN KEBISINGAN DAN TEKANAN PANAS DENGAN STRES KERJA PADA PEKERJA MEBEL BAGIAN MILLING DI PT ALIS JAYA CIPTATAMA KLATEN - Yemima Kasilva Justin (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Heat stress and noise are two common causes of work accidents that can have psychological effects, one of which is work stress. Based on preliminary studies, the milling section exceeds NAB with noise exceeding 85 dB and heat pressure exceeding 28 ºC. From the results of the questionnaire analysis, 8 out of 10 workers experienced moderate work stress due to noise, and 7 out of 10 workers were experiencing moderate work stress due to heat stress. This study aimed to find out the relationship between noise exposure and heat stress to work stress on furniture workers at the milling work station at PT Alis Jaya Ciptatama, Klaten. This research is an observational analytic study with a cross-sectional approach. Research respondents numbered 50 people taken with total sampling techniques. Data collection techniques use noise and heat stress measurements and questionnaires. Data analysis uses the Chi-Square statistical test. The result of this study, namely variables related to work stress, is heat stress (p-value 0.001) and unrelated noise (p-value 0.470). It can be concluded that there is no relationship between noise and work stress at PT Alis Jaya Ciptatama milling section workers with a p-value of 0.470 and there is a relationship between heat stress and work stress at PT Alis Jaya Ciptatama milling section workers with a p-value of 0.001. The suggestions can be done by administrative control with worker rotation, adding ventilator turbines, providing training to workers in overcoming heat stress stressors.